The impact of robots in Latin America: evidence from local labor markets - Brambilla, Irene (2023)
We study the effect of robots on labor markets in Argentina, Brazil, and Mexico, the major robot users in Latin America, during the period 2004-2016. We exploit spatial and time variations in exposure to robots arising from initial differences in industry specialization across geographic locations and the evolution of robot adoption across industries, to estimate a causal effect of robots on local labor market outcomes. We find that district’s exposure to robots causes a relative deterioration in labor market indicators such us unemployment and labor informality. We document that robots mainly replace formal salaried jobs, affecting young and semi-skilled workers to a greater extent, and that informal employment acts as a buffer that prevents a larger increase in unemployment.